A Nona‐nuclear Heterometallic Pd3Pt6 "Donut"‐Shaped Cage: Molecular Recognition and Photocatalysis. (7th June 2018) - Preston, Dan; Sutton, Joshua J.; Gordon, Keith C.; Crowley, James D.
Abstract: We report a simple, low‐symmetry 2‐(1‐(pyridine‐4‐methyl)‐1 H ‐1, 2, 3‐triazol‐4‐yl)pyridine ligand that has both monodentate and bidentate binding sites. With platinum(II) and/or palladium(II) ions, two examples of a new nona‐nuclear metallo‐assembly have been accessed. These complexes were characterized by NMR spectroscopy, electrospray mass spectrometry (ESI‐MS), and in key cases, X‐ray crystallography. The cages possess three clefts comprised of planar cationic panels. This structural feature enables the binding of planar aromatic guests such as anthracene. More interestingly, the heterometallic assembly was able to catalyze the light‐induced [4+2] cycloaddition of anthracene with singlet oxygen. Abstract : Ein katalytischer Donut : Ein neunkerniger Pd II /Pt II ‐Heterometallkäfig bindet Anthracenmoleküle und katalysiert ihre Umwandlung in Endoperoxide durch die Produktion von Singulett‐Sauerstoff in Gegenwart von Licht.